Morphological character analysis of Rasbora borneensis - Pratama, Sandi Fransisco; Yuyun Nisaul, Khairillah; Pasmawati, Pasmawati; Fitriagustiani, Fitriagustiani (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2023)
Rasbora borneensis is a local fish of West Kalimantan that has the potential to be developed as farmed fish and biomedical research model animals. The utilization of fish potential as aquaculture animals and biomedical research model animals requires data on the biological aspects of these fish. Data from Fish Base (2023) shows that until now the biological information of Rasbora borneensis is still very limited, both morphological, anatomical, and reproductive data. This study aims to analyze the morphological characters of Rasbora borneensis. The results of this study show that there are morphological differences between male and female Rasbora borneensis fish. Female fish show a rounded flat body shape, while male fish show a flat body shape. The measurement results show that the morphometric ratio of male and female fish is different. However, when viewed based on variations in the size of the specimens used, there are several sizes that have the same value.